Core inflation as an auxiliary target in the achievement of the primary inflation target in Poland - Filar, Dariusz (Journal of Public Governance, 2012)
In many countries, including Poland, central banks have adopted the monetary policy strategy known as inflation targeting. Usually, inflation targets are formulated as a given level of consumer price index (CPI). However, this measure includes food and energy prices, which are almost entirely beyond the impact of monetary policy decisions. Thus, while shaping monetary policy reactions, it seems justified to take into account core infl ation (excluding food and energy prices).